A Note on Fisher Hypothesis and Price Level Uncertainty - Amihud, Y.; Barnea, A. (Journal of Financial and Quantitative Analysis, 1977)
The theory on the relationship between real and nominal interest rates is based on the well-known Fisher equation:where: i = nominal interest rate;r = real interest rate;λ = percentage change in price level: P /P0 - 1 where P and P0 denote end-of-period and current levels of some aggregate price index, respectively.